Preparation method of iron-based cocatalyst modified bismuth vanadate photo-anode

By introducing oxygen vacancies and the iron-based cocatalyst NiFeOX on the BiVO4 photoanode, the problems of slow charge migration and easy recombination of electron hole pairs in the BiVO4 photoanode are solved, which significantly improves the performance and stability of PEC decomposition of water.

CN119465272AInactive Publication Date: 2025-02-18NANJING TECH UNIV

Patent Information

Application Number
CN202411636491.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The performance of BiVO4 photoanode in PEC decomposition water is limited by problems such as slow charge migration and easy recombination of electrons and holes, which leads to its performance not ideal.

Method used

The oxygen vacancy was introduced by chemical reduction method, and the iron-based cocatalyst NiFeOX was loaded on the surface of BiVO4 by chemical bath deposition method to form a BiVO4-OV-NiFeOX photoanode.

Benefits of technology

It significantly improves the photoelectrocatalytic performance and stability of BiVO4 photoanode, improves the photocurrent density and water oxidation performance, and enhances the carrier separation and transfer capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465272A_ABST
    Figure CN119465272A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an iron-based cocatalyst modified bismuth vanadate photo-anode, which belongs to a photo-anode preparation technology and comprises the following steps: firstly, introducing oxygen vacancies to the surface of BiVO4 through chemical reduction by using a mild reducing agent sodium sulfite (Na2SO3) under a low-temperature condition by a simple chemical reduction method; the introduction of oxygen vacancies improves the charge transfer efficiency and the carrier separation efficiency. And then loading the NiFeOX nano thin layer on the surface of BiVO4, and optimizing the loading capacity of the cocatalyst by adjusting the reaction time. BiVO4 is cooperatively modified through oxygen vacancies and a cocatalyst NiFeOX. And a feasible strategy is provided for simply designing and preparing a high-performance and high-durability BiVO4-based photo-anode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photoanode materials, and in particular relates to a method for preparing a bismuth vanadate photoanode modified by an iron-based promoter. Background Art

[0002] Bismuth vanadate (BiVO4) is one of the new and promising photoanode materials for PEC water splitting due to its low cost, high visible light utilization rate and strong catalytic performance. However, the slow charge migration at the photoanode-electrolyte interface of BiVO4 and the easy recombination of electron-hole pairs have led to unsatisfactory performance of PEC water splitting. In order to improve the photoelectrocatalytic performance, researchers have conducted extensive research on synthesis schemes, structural optimization, doping processes and heterojunction construction.

[0003] BiVO4 is a promising photoanode material for photoelectrochemical water splitting, but the development of pure BiVO4 is limited by its poor conductivity, easy recombination of electron-hole pairs, short carrier diffusion length, short visible light response range (less than 520nm), and slow water oxidation kinetics. In order to optimize the PEC performance of photoanode BiVO4, the main modification technologies include doping process, heterojunction construction, catalyst deposition, vacancy introduction and crystal surface engineering. These strategies mainly improve the separation and transfer ability of carriers from the aspects of band gap, interface effect, stability and defects, thereby improving the PEC performance of BiVO4 materials.

[0004] Studies have shown that material defects can cause great changes in the structure and properties of materials. Appropriate defect introduction can adjust the electronic structure of semiconductors, increase conductivity and mobility, etc., and have a positive effect on photocatalytic activity. In particular, the introduction of oxygen vacancies in BiVO4 removes oxygen atoms from the lattice and generates oxygen vacancies, thereby generating sub-band gaps. Oxygen vacancies reduce the starting potential in the OER reaction, reduce the band gap, and thus enhance light absorption, promoting charge transfer and separation. At present, the effective methods for making oxygen vacancies on BiVO4 materials are: heat treatment under reducing / inert atmosphere, chemical reduction, heteroatom doping, electrochemical reduction, etc. Compared with heteroatom doping and electrochemical reduction methods, heat treatment under reducing / inert atmosphere and chemical reduction are two relatively simple methods for making oxygen vacancies. However, the generation of oxygen vacancies by heat treatment under reducing / inert atmosphere requires more stringent reaction conditions. This method requires the BiVO4 material to be annealed at high temperature in a H2 / Ar mixed gas or pure Ar gas atmosphere, and the annealing temperature is between 200-700 °C. In comparison, the chemical reduction method has milder reaction conditions and simpler experimental operations, making it a more suitable industrial treatment method.

[0005] In addition to vacancy defect modification of BiVO4 photoanode, many studies in recent years have reported feasible methods for modifying BiVO4 photoanode, including doping, heterostructure construction, morphology control and loading of co-catalyst modification. In view of the slow charge migration at the photoanode-electrolyte interface of BiVO4 and the easy recombination of electron-hole pairs, loading co-catalysts to modify BiVO4 can effectively promote the oxygen evolution reaction kinetics at the electrode-electrolyte interface, and is also the most effective method to promote charge transfer at the BiVO4 photoanode. After modification, the co-catalyst effectively reduces the catalyst overpotential, accelerates charge transfer and separation, and provides more reactive centers, thus significantly enhancing the PEC water splitting performance. Typical oxygen evolution co-catalysts, such as oxyhydroxides (FeOOH, CoOOH, NiOOH), transition metal oxides (CoO x , MnO x , IrO x ) and cobalt-based compounds (CoPi, CoOI) can provide abundant active centers. In addition, metal organic frameworks (MOFs) can also be used as co-catalysts to modify BiVO4 photoanodes. The BiVO4 photoanodes modified with MOFs have higher specific surface areas and unsaturated metal centers, which can also effectively improve the PEC water decomposition performance of BiVO4 photoanodes. However, the synthesis process of MOF materials is complicated and the synthetic precursors are expensive, so they are not ideal modified materials for industrial applications. In comparison, among the many co-catalysts, iron-based and nickel-based co-catalysts have higher efficiency and lower cost, but the interfacial interaction between the co-catalysts and BiVO4 and the role of the co-catalysts in the water oxidation process are still controversial. Therefore, it is very important to understand the interaction between the photoanode and the co-catalyst and to construct a high-performance and durable photoanode.

[0006] Although BiVO4 research has made great progress and achievements, it still cannot meet industrial needs. BiVO4 faces three main challenges. First, the actual photocurrent is different from the theoretical photocurrent of 7.5 mA cm 2 There is still a certain gap. Therefore, more modification schemes should be developed to improve the activity of BiVO4 as a photoanode. Secondly, the stability of BiVO4 is also very important. Many modification methods only improve the activity of BiVO4 but ignore the improvement of stability, especially far from the requirements of commercial PEC water decomposition. Next, the size of the BiVO4 photoanode studied in the laboratory remains at the centimeter level. The preparation of large-area PEC materials is the key to practical application. Currently, BiVO4 is mainly prepared by electroplating, but the material obtained by this method is small in area and uneven. Summary of the invention

[0007] In order to solve the above technical problems, the present invention discloses a method for preparing a bismuth vanadate photoanode modified with an iron-based co-catalyst, and the specific technical scheme is as follows.

[0008] A method for preparing a bismuth vanadate photoanode modified with an iron-based promoter comprises the following steps: Step 1: dissolving bismuth nitrate pentahydrate in dilute nitric acid, and sequentially adding ammonium metavanadate and polyvinyl alcohol, and mixing to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: preparing a dilute nitric acid solution of bismuth nitrate pentahydrate and ammonium metavanadate, and mixing them to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the seed layer downward in the mixed solution, and react in a high-pressure reactor. After the reaction, wash the sample with deionized water and anneal to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain a BiVO4 nanofilm photoanode with impurities removed; Step 5: Place the BiVO4 nanofilm photoanode in a Na2SO3 solution for reaction. After the reaction, wash it with deionized water and dry it to obtain an oxygen vacancy sample, which is recorded as BiVO4-O V ; Step 6: prepare FeCl3·6H2O and NiCl2·6H2O solutions, and quickly mix and stir them to obtain a fresh mixed metal salt acid solution; Step 7: BiVO4-O V The photoanode was immersed in a fresh mixed metal salt acid solution, and the pH of the solution was adjusted to 8. The reaction was carried out at room temperature. After the reaction was completed, it was washed with deionized water and dried to obtain BiVO4-O V -NiFeO X .

[0009] Furthermore, the mixing in step 1 and step 3 is performed by ultrasound and / or stirring.

[0010] Furthermore, the method for treating the cleaned FTO glass is to firstly put the FTO glass into a solution of acetone, ethanol and deionized water for ultrasonic treatment, and then put it into an oven for drying after washing.

[0011] Furthermore, the immersion time in step 2 is 20 s.

[0012] Furthermore, the heat treatment temperature in step 2 is 450 °C and the treatment time is 2 h.

[0013] Furthermore, the reaction conditions in step 4 are 180 °C for 12 h.

[0014] Furthermore, the high-pressure reactor in step 4 contains a polytetrafluoroethylene lining, the mixed liquid and FTO glass are placed in the lining and heated in a blast oven.

[0015] Furthermore, the annealing temperature in step 4 is 450°C, and the heating is carried out in a muffle furnace.

[0016] Furthermore, the reaction conditions and duration of step 5 are 60 ° C and 24 h respectively.

[0017] Furthermore, the drying temperature in step 2, step 4, step 5 and step 7 is 70°C and is heated in an oven.

[0018] Compared with the prior art, (1) the present invention uses a simple chemical bath deposition method to deposit the catalyst NiFeO X Loaded on BiVO4-O V Photoanode, NiFeO was prepared as a comparison X Loaded on the surface of pure BiVO4, the co-catalyst NiFeO X For pure BiVO4 and BiVO4-O V Performance impact. BiVO4-NiFeO at 1.23 V vs. RHE X The photocurrent density is 1.6 mAcm −2 , which is 4 times the performance of pure BiVO4. Composite photoanode BiVO4-O V -NiFeO X -90 photoanode has excellent photocurrent density and can reach 1.9 mA cm −2 , which is 4.75 times the performance of pure BiVO4, indicating that the ultra-thin structure of the catalyst NiFeO X The photocurrent of the sample can be significantly improved. On the one hand, the ultra-thin structure can effectively promote hole transport, reduce surface charge recombination, and increase the number of surface active centers; on the other hand, NiFeO X The abundant oxygen vacancies in the catalyst promote the separation and transfer of charges. The oxygen vacancies obtained by chemical reduction and the co-catalyst NiFeO X The synergistic effect can further promote the photocurrent, and the charge injection efficiency of the modified composite photoelectrode is 89% and the separation efficiency is 40%. The invention significantly improves the photoelectrocatalytic performance of BiVO4 by preparing the photoanode through a simple method.

[0019] (2) In the present invention, the 12 h photocurrent density stability test curve shows that NiFeO X The modified BiVO4-O V -NiFeO X-90 The good PEC water oxidation performance is due to the Fe site effectively capturing photogenerated holes to accelerate the PEC process; the good chemical stability is due to the Ni site injecting electrons into the V in the BiVO4 lattice, inhibiting V 5+ Ultra-thin NiFeO X The BiVO4 surface is passivated by a layer, which significantly inhibits the recombination of surface electrons and holes, enhances hole injection, and thus improves the water splitting performance. V -NiFeO X -90 photocurrent decreased by 9.4%, indicating that the use of NiFeO X The modified BiVO4 photoanode has better stability.

[0020] (3) In the present invention, oxygen vacancies and NiFeO X The photocurrent starting potential is negatively shifted by 0.207 eV, which not only can obtain a higher photocurrent density at a lower bias voltage but also can effectively improve the PEC water splitting activity. At the same time, the band structure position of the composite sample is obtained from the UV and Mott Schottky curves, indicating that the reduced band gap of the modified sample can increase the utilization rate of light.

[0021] (4) In the present invention, oxygen vacancy defects and the promoter NiFeO X The co-modified BiVO4 photoanode significantly improved the PEC water splitting performance and stability of the BiVO4 photoanode under neutral reaction conditions. Compared with the existing BiVO4 photoanode modification strategy, we prepared oxygen vacancy defects and co-catalyst NiFeO by simple chemical reduction and chemical bath deposition. X The co-modified BiVO4 photoanode has a simpler preparation process and milder synthesis conditions. At the same time, we use low-cost co-catalyst NiFeO X To modify the BiVO4 photoanode, the synthesis cost of BiVO4-based photoanode is greatly reduced.

[0022] (5) The present invention uses oxygen vacancy defects and co-catalyst NiFeO X The photoelectrocatalytic performance and hydrogen production of the co-modified BiVO4 photoanode are achieved in a neutral solution, while similar materials in the prior art need to be achieved under alkaline conditions, which reduces costs for future large-scale applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 BiVO4 photoanode and BiVO4-O V -NiFeO X -90 SEM schematic diagram of the photoanode; Figure 2 For example, BiVO4-OV -NiFeO X -90 and BiVO4-NiFeO X O 1s spectrum of X-ray photoelectron spectroscopy; Figure 3 Schematic diagram of linear sweep voltammetry curve of an example; Figure 4 BiVO4-O V -NiFeO X Schematic diagram of the photoelectrochemical water splitting performance and stability of -90 for hydrogen production. DETAILED DESCRIPTION

[0024] The following is a clear and complete description of the technical solutions in the examples of the present invention. Obviously, the examples described are only part of the examples of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The following experimental methods and detection methods are conventional methods unless otherwise specified; the following reagents and raw materials are commercially available unless otherwise specified.

[0026] Example 1 Step 1: Dissolve 0.323 g of bismuth nitrate pentahydrate in 1 mL of concentrated nitric acid (63%) and 2 mL of deionized water, and add 0.078 g of ammonium metavanadate and 0.167 g of polyvinyl alcohol in sequence, and mix to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution described in step 1, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: Dissolve 0.116 g of bismuth nitrate pentahydrate and 0.028 g of ammonium metavanadate in 56 mL of deionized water and 4 mL of concentrated nitric acid, and mix to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the BiVO4 seed layer described in step 2 in a downward tilted position in 10 mL of the mixed solution described in step 3, and react in a high-pressure reactor at 180 °C for 12 h. After the reaction, wash the sample with deionized water, place the sample in a muffle furnace and anneal it at 450 °C for 2 h to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain a BiVO4 nanofilm photoanode with impurities removed; Step 5: Place the BiVO4 nanofilm photoanode in a 0.5 M Na2SO3 solution and react at 60 °C for 24 h. After the reaction, wash with deionized water and dry to obtain a sample. Step 6: Prepare 5 mL of 10 mM FeCl3·6H2O and 15 mL of 10 mM NiCl2·6H2O solution, and quickly mix and stir them to obtain a fresh mixed metal salt acid solution; Step 7: Soak the sample described in step 5 in the fresh mixed metal salt acid solution described in step 6 for 15 min, adjust the pH to 8 with 2 M NaOH solution, and react at room temperature for 30, 60, 90 and 120 min respectively. After the reaction, wash with deionized water and dry to obtain the photoanode material BiVO4-O V -NiFeO X -30, BiVO4-O V -NiFeO X -60、BiVO4-O V -NiFeO X -90 and BiVO4-O V -NiFeO X -120.

[0027] Step 8: PEC performance was measured using a typical three-electrode setup on a CHI660E electrochemical workstation (Shanghai Chenhua). The photoanode material, Ag / AgCl (saturated potassium chloride) and Pt wire were used as the working electrode, reference electrode and counter electrode, respectively. The light source was a 300W Xe lamp (CHF-XM300). The photoelectrochemical performance of the sample was analyzed by sunlight simulated by an AM 1.5G filter. The test light intensity was stable at 100 mW•cm -2 , the test area is 1.5cm 2 . PEC measurement was performed using 0.5M Na2SO4 solution (pH=7) as the electrolyte.

[0028] The photoanode material prepared in this example was tested by PEC, and the photocurrent density was as follows Figure 3 (a) Under AM 1.5G illumination (100 mW cm -2 ) and 0.5 M Na2SO4 (pH = 7) electrolyte conditions, BiVO4-O V -NiFeO X -90 has the highest photocurrent, with the highest photocurrent being 1.9 mA cm −2 .

[0029] Example 2 Step 1: Dissolve 0.323 g of bismuth nitrate pentahydrate in 1 mL of concentrated nitric acid (63%) and 2 mL of deionized water, and add 0.078 g of ammonium metavanadate and 0.167 g of polyvinyl alcohol in sequence, and mix to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution described in step 1, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: Dissolve 0.116 g of bismuth nitrate pentahydrate and 0.028 g of ammonium metavanadate in 56 mL of deionized water and 4 mL of concentrated nitric acid, and mix to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the BiVO4 seed layer described in step 2 in a downward tilted position in 10 mL of the mixed solution described in step 3, and react in a high-pressure reactor at 180°C for 12 h. After the reaction, wash the sample with deionized water, place the sample in a muffle furnace and anneal it at 450°C for 2 h to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain a BiVO4 nanofilm photoanode with impurities removed; Step 5: Place the BiVO4 nanofilm photoanode in 0.2, 0.5 and 1 M Na2SO3 solutions respectively, react at 60 °C for 24 h, wash with deionized water after the reaction, and dry to obtain the photoanode material BiVO4-O V -0.2、BiVO4-O V -0.5 and BiVO4-O V -1; Step 6: PEC performance was measured using a typical three-electrode setup on a CHI660E electrochemical workstation (Shanghai Chenhua). The photoanode material, Ag / AgCl (saturated potassium chloride) and Pt wire were used as the working electrode, reference electrode and counter electrode, respectively. The light source was a 300W Xe lamp (CHF-XM300). The photoelectrochemical performance of the sample was analyzed by sunlight simulated by an AM 1.5G filter. The test light intensity was stable at 100 mW•cm -2 , the test area is 1.5cm 2 . PEC measurement was performed using 0.5M Na2SO4 solution (pH=7) as the electrolyte.

[0030] The photoanode material prepared in this example was tested by PEC, and the photocurrent density was as follows Figure 3 (b) Under AM 1.5G illumination (100 mW cm -2 ) and 0.5 M Na2SO4 (pH = 7) electrolyte conditions, BiVO4-O V -0.5 has the highest photocurrent, with the highest photocurrent being 0.6 mA cm −2 .

[0031] Example 3 Step 1: Dissolve 0.323 g of bismuth nitrate pentahydrate in 1 mL of concentrated nitric acid (63%) and 2 mL of deionized water, and add 0.078 g of ammonium metavanadate and 0.167 g of polyvinyl alcohol in sequence, and mix to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution described in step 1, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: Dissolve 0.116 g of bismuth nitrate pentahydrate and 0.028 g of ammonium metavanadate in 56 mL of deionized water and 4 mL of concentrated nitric acid, and mix to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the BiVO4 seed layer described in step 2 in a downward tilted position in 10 mL of the mixed solution described in step 3, and react in a high-pressure reactor at 180°C for 12 h. After the reaction, wash the sample with deionized water, place the sample in a muffle furnace and anneal it at 450°C for 2 h to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain the photoanode material BiVO4 with impurities removed; Step 5: PEC performance was measured using a typical three-electrode setup on a CHI660E electrochemical workstation (Shanghai Chenhua). The photoanode material, Ag / AgCl (saturated potassium chloride) and Pt wire were used as the working electrode, reference electrode and counter electrode, respectively. The light source was a 300W Xe lamp (CHF-XM300). The photoelectrochemical performance of the sample was analyzed by sunlight simulated by an AM 1.5G filter. The test light intensity was stable at 100 mW•cm -2 , the test area is 1.5cm 2 . PEC measurement was performed using 0.5M Na2SO4 solution (pH=7) as the electrolyte.

[0032] The photoanode material prepared in this example was tested by PEC, and the photocurrent density was as follows Figure 3 (c) Under AM 1.5G illumination (100 mW cm -2 ) and 0.5 M Na2SO4 (pH = 7) electrolyte conditions, the maximum photocurrent of BiVO4 is 0.4 mA cm −2 .

[0033] Example 4 Step 1: Dissolve 0.323 g of bismuth nitrate pentahydrate in 1 mL of concentrated nitric acid (63%) and 2 mL of deionized water, and add 0.078 g of ammonium metavanadate and 0.167 g of polyvinyl alcohol in sequence, and mix to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution described in step 1, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: Dissolve 0.116 g of bismuth nitrate pentahydrate and 0.028 g of ammonium metavanadate in 56 mL of deionized water and 4 mL of concentrated nitric acid, and mix to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the BiVO4 seed layer described in step 2 in a downward tilted position in 10 mL of the mixed solution described in step 3, and react in a high-pressure reactor at 180°C for 12 h. After the reaction, wash the sample with deionized water, place the sample in a muffle furnace and anneal it at 450°C for 2 h to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain a BiVO4 nanofilm photoanode with impurities removed; Step 5: Prepare 20 mL of 10 mM FeCl3·6H2O metal salt acid solution; Step 6: Soak the sample described in step 4 in the fresh mixed metal salt acid solution described in step 5 for 15 min, adjust the pH to 8 with 2 M NaOH solution, and react at room temperature for 90 min. After the reaction, wash with deionized water and dry to obtain the photoanode material BiVO4-FeO X .

[0034] Step 7: PEC performance was measured using a typical three-electrode setup on a CHI660E electrochemical workstation (Shanghai Chenhua). The photoanode material, Ag / AgCl (saturated potassium chloride) and Pt wire were used as the working electrode, reference electrode and counter electrode, respectively. The light source was a 300W Xe lamp (CHF-XM300). The photoelectrochemical performance of the sample was analyzed by sunlight simulated by an AM 1.5G filter. The test light intensity was stable at 100 mW•cm -2 , the test area is 1.5cm 2 . PEC measurement was performed using 0.5M Na2SO4 solution (pH=7) as the electrolyte.

[0035] The photoanode material prepared in this example was tested by PEC, and the photocurrent density was as follows Figure 3 (c) Under AM 1.5G illumination (100 mW cm -2 ) and 0.5 M Na2SO4 (pH = 7) electrolyte conditions, BiVO4-FeO X The highest photocurrent is 0.8 mA cm −2 .

[0036] Example 5 Step 1: Dissolve 0.323 g of bismuth nitrate pentahydrate in 1 mL of concentrated nitric acid (63%) and 2 mL of deionized water, and add 0.078 g of ammonium metavanadate and 0.167 g of polyvinyl alcohol in sequence, and mix to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution described in step 1, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: Dissolve 0.116 g of bismuth nitrate pentahydrate and 0.028 g of ammonium metavanadate in 56 mL of deionized water and 4 mL of concentrated nitric acid, and mix to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the BiVO4 seed layer described in step 2 in a downward tilted position in 10 mL of the mixed solution described in step 3, and react in a high-pressure reactor at 180°C for 12 h. After the reaction, wash the sample with deionized water, place the sample in a muffle furnace and anneal it at 450°C for 2 h to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain a BiVO4 nanofilm photoanode with impurities removed; Step 5: Prepare 20 mL of 10 mM NiCl2·6H2O metal salt acid solution; Step 6: Soak the sample described in step 4 in the fresh mixed metal salt acid solution described in step 5 for 15 min, adjust the pH to 8 with 2 M NaOH solution, and react at room temperature for 90 min. After the reaction, wash with deionized water and dry to obtain the photoanode material BiVO4-NiO X .

[0037] Step 7: PEC performance was measured using a typical three-electrode setup on a CHI660E electrochemical workstation (Shanghai Chenhua). The photoanode material, Ag / AgCl (saturated potassium chloride) and Pt wire were used as the working electrode, reference electrode and counter electrode, respectively. The light source was a 300W Xe lamp (CHF-XM300). The photoelectrochemical performance of the sample was analyzed by sunlight simulated by an AM 1.5G filter. The test light intensity was stable at 100 mW•cm -2 , the test area is 1.5cm 2 . PEC measurement was performed using 0.5M Na2SO4 solution (pH=7) as the electrolyte.

[0038] The photoanode material prepared in this example was tested by PEC, and the photocurrent density was as follows Figure 3 (c) Under AM 1.5G illumination (100 mW cm -2 ) and 0.5 M Na2SO4 (pH = 7) electrolyte conditions, BiVO4-NiOX The highest photocurrent is 0.4 mA cm −2 .

[0039] Example 6 Step 1: Dissolve 0.323 g of bismuth nitrate pentahydrate in 1 mL of concentrated nitric acid (63%) and 2 mL of deionized water, and add 0.078 g of ammonium metavanadate and 0.167 g of polyvinyl alcohol in sequence, and mix to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution described in step 1, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: Dissolve 0.116 g of bismuth nitrate pentahydrate and 0.028 g of ammonium metavanadate in 56 mL of deionized water and 4 mL of concentrated nitric acid, and mix to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the BiVO4 seed layer described in step 2 in a downward tilted position in 10 mL of the mixed solution described in step 3, and react in a high-pressure reactor at 180°C for 12 h. After the reaction, wash the sample with deionized water, place the sample in a muffle furnace and anneal it at 450°C for 2 h to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain a BiVO4 nanofilm photoanode with impurities removed; Step 5: Prepare 5 mL of 10 mM FeCl3·6H2O and 15 mL of 10 mM NiCl2·6H2O solution, and quickly mix and stir them to obtain a fresh mixed metal salt acid solution; Step 6: Soak the sample described in step 4 in the fresh mixed metal salt acid solution described in step 5 for 15 min, adjust the pH to 8 with 2 M NaOH solution, and react at room temperature for 30, 60, 90 and 120 min respectively. After the reaction, wash with deionized water and dry to obtain photoanode materials BiVO4-NiFeO X -30, BiVO4-NiFeO X -60, BiVO4-NiFeO X -90 and BiVO4-NiFeO X -120.

[0040] Step 7: PEC performance was measured using a typical three-electrode setup on a CHI660E electrochemical workstation (Shanghai Chenhua). The photoanode material, Ag / AgCl (saturated potassium chloride) and Pt wire were used as the working electrode, reference electrode and counter electrode, respectively. The light source was a 300W Xe lamp (CHF-XM300). The photoelectrochemical performance of the sample was analyzed by sunlight simulated by an AM 1.5G filter. The test light intensity was stable at 100 mW•cm -2 , the test area is 1.5cm 2 . PEC measurement was performed using 0.5M Na2SO4 solution (pH=7) as the electrolyte.

[0041] The photoanode material prepared in this example was tested by PEC, and the photocurrent density was as follows Figure 3 (d) Under AM 1.5G illumination (100 mW cm -2 ) and 0.5 M Na2SO4 (pH = 7) electrolyte conditions, BiVO4-NiFeO X -90 has the highest photocurrent, with a maximum photocurrent of 1.6 mA cm −2 .

[0042] The photoanode materials described in the above examples were subjected to the following characterization tests: from Figure 1 The scanning electron microscope diagram shows that the BiVO4 nanofilm has a smooth surface, an average particle size of 1 μm, and a thickness of about 1.5 μm. Chemical reduction and chemical bath deposition methods introduce oxygen vacancies and load the co-catalyst NiFeO on the surface of the BiVO4 photoanode. X , NiFeO X After the co-catalyst was loaded, the photoanode BiVO4-O V -NiFeO X The surface changes from smooth to rough, indicating that NiFeO X Successful loading of co-catalyst.

[0043] from Figure 2 It can be seen that the O 1s spectra of the high-resolution fine spectra of the two examples can analyze the peaks of lattice oxygen, oxygen vacancies and water molecules adsorbed oxygen. X , for example BiVO4-O V -NiFeO X -90 has a larger area of ​​vacancy oxygen peak, indicating that oxygen vacancies were successfully introduced into BiVO4-O by chemical reduction. V -NiFeO X On the photoanode.

[0044] from Figure 3It can be seen that compared with other examples, the BiVO4-O V -NiFeO X -90 has a larger photocurrent density, which is due to the oxygen vacancy defects and the co-catalyst NiFeO X The co-modified BiVO4 photoanode significantly improved the PEC water splitting performance and stability of the BiVO4 photoanode under neutral reaction conditions.

[0045] Figure 4 BiVO4-O is an example of the best photoanode performance under simulated sunlight illumination. V -NiFeO X -90 was used for PEC water decomposition to produce hydrogen content, rate and stability. Figure 4 a is the photocurrent of the sample before and after three cycles of hydrogen production. After long-term illumination and electrolyte immersion, the photocurrent density before and after the cycle decreased by only 0.32 mA cm at 1.23 V vs. RHE. −2 , indicating that the photocurrent performance remains good. Figure 4 As shown in b, BiVO4-O V -NiFeO X -90 produced hydrogen with a content of 113.6 μmol·cm −2 The hydrogen production rate is 28.4 μmol·cm −2 ·h −1 , Figure 4 The hydrogen production rate curve of BiVO4-O V -NiFeO X The hydrogen production rate of the second cycle of the -90 photoanode was well maintained, and the hydrogen production rate of the third cycle was 86.5% of the first cycle, indicating that the BiVO4-O V -NiFeO X -90 The photoanode has good cycle stability in producing hydrogen.

[0046] In order to understand the stability of the modified composite photoanode, the BiVO4-O V -NiFeO X -90 12 h photocurrent performance curve, from Figure 4 (d) The test results show that the photocurrent of the sample before cycling is 1.6 mA cm −2 After the cycle, the photocurrent was 1.45 mA cm −2 , indicating that the photocurrent decreased by 9.4%. This indicates that the catalyst NiFeO X It is beneficial to improve the chemical stability of BiVO4. The cycle curve of hydrogen production and the 12 h photocurrent stability test both prove that BiVO4-O V-NiFeO X -90 Good stability of the sample.

[0047] In the present invention, oxygen vacancies are first introduced into the surface of BiVO4 by chemical reduction using a mild reducing agent, sodium sulfite (Na2SO3), under low temperature conditions. The introduction of oxygen vacancies improves the charge transfer efficiency and carrier separation efficiency. Then, NiFeO X The nano-thin layer is loaded on the BiVO4 surface, and the loading amount of the co-catalyst is optimized by adjusting the reaction time. X Synergistic modification of BiVO4.

[0048] The study found that the chemically introduced oxygen vacancies in the synergistic process play a role in improving conductivity and accelerating hole transfer; the co-catalyst NiFeO X Fe ions stabilize Ni 2+ , promoting water oxidation reaction. Ni ions can inhibit V 5+ dissolve, inhibiting photocorrosion. Therefore, the PEC performance and stability of the composite photoanode are promoted. In addition, oxygen vacancies and co-catalyst NiFeO X Compared with the single BiVO4 photoanode, the photoelectrochemical water splitting performance of the composite photoanode is significantly improved by synergistic modification of BiVO4. The synergistic effect of oxygen vacancies and NiFeOx loading can enhance the separation of electron-hole pairs and promote the transfer of charges.

[0049] In addition, the abundant surface oxygen vacancies in the ultrathin NiFeOx structure can also serve as active centers for hole transport layer to enhance charge separation and water oxidation, making BiVO4-O V -NiFeO X It has good stability and reaction kinetics of PEC water oxidation, thereby improving the PEC water splitting performance of BiVO4 film.

[0050] The present invention prepares the BiVO4 photoanode by a simple hydrothermal method, and creates oxygen vacancies on the BiVO4 photoanode by a simpler chemical reduction method, and then uses a low-cost co-catalyst (NiFeO X ) modified BiVO4 photoanode and prepared a BiVO4 photoanode material modified with an iron-based co-catalyst (BiVO4-O V -NiFeO X ). Compared with a single BiVO4 photoanode, its PEC water decomposition performance for hydrogen production is significantly improved, and the stability of the BiVO4 photoanode material is effectively improved. And because the synthesis method is simpler, it is expected to be applied to the large-scale and efficient preparation of BiVO4 photoanode materials. This invention provides a feasible strategy for the design and preparation of high-performance and high-durability BiVO4-based photoanode materials.

Claims

1. A method for preparing a bismuth vanadate photoanode modified with an iron-based promoter, characterized in that: The following steps are involved: Step 1: dissolving bismuth nitrate pentahydrate in dilute nitric acid, and sequentially adding ammonium metavanadate and polyvinyl alcohol, and mixing to obtain a precursor solution; Step 2: Immerse the cleaned FTO glass in the precursor solution, then dry it, and heat-treat it in air to obtain a BiVO4 seed layer; Step 3: preparing a dilute nitric acid solution of bismuth nitrate pentahydrate and ammonium metavanadate, and mixing them to obtain a mixed solution; Step 4: Place the conductive surface of the FTO glass containing the seed layer downward in the mixed solution, and react in a high-pressure reactor. After the reaction, wash the sample with deionized water and anneal to obtain a BiVO4 nanofilm photoanode; soak the BiVO4 nanofilm photoanode in an alkaline solution, rinse it with deionized water, and dry it to obtain a BiVO4 nanofilm photoanode with impurities removed; Step 5: Place the BiVO4 nanofilm photoanode in a Na2SO3 solution for reaction. After the reaction, wash it with deionized water and dry it to obtain an oxygen vacancy sample, which is recorded as BiVO4-O V ; Step 6: prepare FeCl3·6H2O and NiCl2·6H2O solutions, and quickly mix and stir them to obtain a fresh mixed metal salt acid solution; Step 7: BiVO4-O V The photoanode was immersed in a fresh mixed metal salt acid solution, and the pH of the solution was adjusted to 8. The reaction was carried out at room temperature. After the reaction was completed, it was washed with deionized water and dried to obtain BiVO4-O V -NiFeO X .

2. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The mixing in step 1 and step 3 is carried out by ultrasound and / or stirring.

3. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The method for treating the cleaned FTO glass is to firstly put the FTO glass into a solution of acetone, ethanol and deionized water for ultrasonic treatment, and then put the FTO glass into an oven for drying after cleaning.

4. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The dipping time in step 2 is 20 s.

5. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The heat treatment temperature in step 2 is 450 °C and the treatment time is 2 h.

6. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The reaction conditions in step 4 are 180 °C for 12 h.

7. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The high-pressure reactor in step 4 contains a polytetrafluoroethylene lining, and the mixed liquid and FTO glass are placed in the lining and heated in a blast oven.

8. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The annealing temperature in step 4 is 450°C, and the annealing is carried out in a muffle furnace.

9. The method for preparing the bismuth vanadate photoanode modified by the iron-based promoter according to claim 1, characterized in that: The reaction conditions and duration of step 5 are 60 ° C and 24 h respectively.

10. The method for preparing the bismuth vanadate photoanode modified with an iron-based promoter according to claim 1, characterized in that: The drying temperature in step 2, step 4, step 5 and step 7 is 70°C, and the drying is carried out in an oven.

Citation Information

Patent Citations

  • Composite bismuth-based photo-anode for photoelectrocatalytic decomposition of water and preparation method of composite bismuth-based photo-anode

    CN112410819A

  • Preparation and application of bismuth vanadate / Vo-FeNiOOH composite photo-anode

    CN113136602A

  • Ferronickel oxide / bismuth vanadate composite photo-anode and preparation method and application thereof

    CN118390104A

  • Bismuth vanadate electrode comprising vanadium-functionalized graphene quantum dots and a preparation method thereof

    US20210108318A1

Cited By

  • Benzene phosphonic acid modified bismuth vanadate photoanode and its preparation and application in selective oxidation of glycerol by photoelectrocatalysis

    CN122773411A